Determination of exploitable efficiency and working conditions of digging machine - Nguyễn Danh Sơn, (Journal of Technical Education Science, 2015)
Efficiency is one of important parameters of machine, which affirm parameters of machine in working conditions. The paper come up with analytic formula to determine exploitable efficiency and working conditions of digging machine. Theoretical formula describes the character of digging progress. She can be used in calculation of digging machine effect and in optimization.